Sequence and sequence-less T-way test suite generation strategy based on flower pollination algorithm - Abdullah, Nasser; Hujainah, Fadhl; Alsewari, Abdulrahman A.; Kamal Z., Zamli (IEEE, 2015)
In an attempt to ensure good-quality software, there is need to test all possible inputs. Owing to the fact that the exhaustive testing is hardly feasible, many software testing approaches has been proposed. Combinatorial Interaction Testing (CIT) is very promising technique to minimize the number of test cases. Although useful, most of exiting CIT strategies and tools focus on data inputs and assume “sequence-less” interactions between input parameters. However, reactive systems show sequence related behaviors and their faults may not expose if the sequence of inputs are not considered. In this paper, we propose a new t-way strategy (i.e. t refers to the degree of the combination) strategy, called Flower Strategy (FS), that addresses both sequence and sequence-less test generation. Experimental results show that FS produces test size.